Sacred Sites as a Threat to Environmental Justice? Environmental Spirituality and Justice Meet among the Diné (Navajo) and Other Indigenous Groups - Cladis, Mark Sydney 1958- (2019)
I explore the intersection of environmental spirituality and environmental justice with special attention given to indigenous ecologies. Indigenous communities often employ the language of discrete "sacred sites" to protect portions of their lands from environmental harm. However, the concept of the sacred in Western traditions is typically accompanied by its binary opposite, the profane. Do protected sacred sites implicitly license harm to such "profane" sites as low-income sacrifice zones? Is environmental spirituality in tension with environmental justice? After explicating this problem, I resolve it by exploring indigenous notions of the sacred—notions that are not binary. Indigenous notions allow for treating some discrete lands as places of special power and healing while still maintaining that all lands are sacred and worthy of environmental protection. These are not hierarchical notions of the sacred but variegated ones (or what I call hózhó sacred weaves).
Keywords: Native American and indigenous religions; Environmental Justice; environmental spirituality; indigenous ecology; Religion; sacred geography; sacred mountains; Sacred Sites